PENDEKATAN UNIQUE POINT SELLING (UPS) DLM REFORMULASI STRATEGI PEMASARAN PULAU GILI TRAWANGAN PASCA GEMPA - I Made Murdana (GANEC SWARA, 2019)
The research was base on the post-earthquake disaster in the island of Lombok. Tourism facilities and infrastructure are damaged and affect the level of tourist visits. This study aims to determine the strategies and action programs in marketing carried out in recovering tourist visits to Gili Trawangan Island in the perspective of a unique selling point (USP). The method used is qualitative descriptive analysis with purposive sumpling through observation and deep interview. The unique selling point approach on Gili Trawangan Island will be reviewed. Based on USP on Gili Trawangan Island, the marketing strategy implemented after the earthquake is reformulation of the strategy, positioning, and imaging of tourist areas. These three strategies are dominantly carried out with the rise of Lombok campaign. Strategically implemented in the marketing of Gili Trawangan Island after the earthquake turned out to be related to unique selling points. UPS is closely related to positioning and imaging strategies. The final result of positioning is the building of regional imagery.